A Coerência das Políticas para o Desenvolvimento: Um instrumento em prol do desenvolvimento? - Patrícia Magalhães Ferreira (Cadernos de Estudos Africanos)
Policy Coherence for Development (PCD) is currently recognised at strategic and normative level as a global policy goal, aiming at integrating development concerns and impacts in the process of defining and implementing policies in several sectoral areas. This concept is gaining importance in international debates and is being increasingly integrated into normative instruments from international and regional organisations, particularly in the Organisation for Economic Cooperation and Development, the United Nations and the European Union. However, the concrete implementation of this approach is still at an early stage, and there seems to be a dissociation between political commitments and the implementation at institutional and monitoring levels, as shown by the brief analysis of external effects of the Common Fisheries Policy and the Common Agricultural Policy.